Policy Strategy for The Use of Cantrang Fishing Tools - Syamsuddin, Azrin; Fauzi, Akhmad (Universitas Djuanda, 2023)
This study aims to: 1) recommendations on the use of cantrang fishing gear (API) in Paciran District, Lamongan Regency, East Java, 2) integrating a participatory approach for the government and cantrang fishermen in their activities. Quantitative method, and purposive sample selection. Data collection October - November 2019. 20 respondents were selected for the multi-criteria assessment. Stakeholders consist of central and regional regulators, fisherman groups in the research location. Stakeholders know the options for action, and produce: 1) program-based evaluation of policies; 2) Evaluation based on Policies to Scenario. Hypotheses: a) Conservation, b) Economy, c) Integration, d) Smartfish. Data were analyzed using Multipol. The revitalization program and product quality are closer to the fish map and fisherman training programs. Conservation policies, closer to infrastructure programs, marine tourism, fish maps, and fishermen training. Each policy scores on the scenario, superior production policies on the demand side scenario, raw material and income policies have a higher score on the supply side scenario. Best average score on revenue policy, followed by raw materials, conservation and production. Income, conservation, production and raw material policies can be implemented in supply-side and demand-side scenarios. Results of Actions and Policy, the highest scores on marine tourism, infrastructure, fishermen training, and fish maps; The results of Action on Policy, marine tourism are determined by fishermen's infrastructure, and the quality of fishermen's products, raw material policies, supporting infrastructure programs, fish maps, and fishermen's training with the highest scores. Development of raw materials, relying on infrastructure, fish map technology, fishermen training, so that fishermen are more reliable. Scenario and Policy Results, policies on income, conservation, production and raw materials, can be implemented in supply side and demand side scenarios (infrastructure and marine tourism).